2014
DOI: 10.1182/blood-2014-03-565721
|View full text |Cite
|
Sign up to set email alerts
|

CD166 regulates human and murine hematopoietic stem cells and the hematopoietic niche

Abstract: Key Points• CD166 identifies human and murine long-term repopulating stem cells.• CD166 is a functional marker of stem cells and the hematopoietic niche.We previously showed that immature CD166

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 39 publications
2
77
0
6
Order By: Relevance
“…3,4 We also showed that this activity is inversely correlated with osteoblast maturation and the level of CD166 expression 4,5 which is a functional marker of murine and human HSCs and niche competency. 6 Our group also demonstrated that megakaryocytes can increase osteoblast proliferation in vitro and in vivo, [7][8][9] thus implicating megakaryocytes, albeit indirectly, in HSC maintenance. These observations identified critical interactions between osteoblasts and megakaryocytes and offered a unique experimental model to assess how megakaryocytes impact HSC function via osteoblasts.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…3,4 We also showed that this activity is inversely correlated with osteoblast maturation and the level of CD166 expression 4,5 which is a functional marker of murine and human HSCs and niche competency. 6 Our group also demonstrated that megakaryocytes can increase osteoblast proliferation in vitro and in vivo, [7][8][9] thus implicating megakaryocytes, albeit indirectly, in HSC maintenance. These observations identified critical interactions between osteoblasts and megakaryocytes and offered a unique experimental model to assess how megakaryocytes impact HSC function via osteoblasts.…”
Section: Introductionmentioning
confidence: 91%
“…Whether these cells (or a different subfraction of OMs) are responsible for the functional properties of OM requires additional investigations. Because we previously demonstrated that CD166 is expressed on HSCs and is critical to the competence of the hematopoietic niche, 6 it is possible that OMs contribute to the fitness of the niche through CD166-CD166 homotypic interactions. It is not clear at present if these homotypic interactions actually take place or whether they involve OMs and HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To verify whether the generalized systemic neutrophilia in the periphery and within organs was due to increased granulopoiesis in the bone marrow, we performed detailed analysis of bone marrow from THP +/+ and THP 2/2 mice using flow cytometry as described [28][29][30] and shown in Figure 3, Supplemental Figure 2. Figure 3A shows a significant decrease in the marrow of THP 2/2 mice of two classes of granulocyte progenitor cells: common myeloid progenitors and granulocyte-macrophage progenitors.…”
Section: Thp Deficiency Causes Enhanced Granulopoiesis In the Bone Mamentioning
confidence: 99%
“…To confirm these data, the osteoblast progenitor populations were assessed by flow cytometric analysis. FACS-based analysis of live (7-AAD 38,39 ( Figure 4C) BM cells demonstrated a significant twofold increase in osteoblasts in TG Rac1 D/D Rac3 2/2 compared with WT mice ( Figure 4D). These findings were further supported by an increase in RNA expression levels of the osteoblast markers osteopontin (Opn) ( Figure 4E), alkaline phosphatase (ALP) (supplemental Figure 3B), and Runx2 (supplemental Figure 3C) …”
Section: The Vascular Endothelial Niche Is Regulated By Rac Proteinsmentioning
confidence: 99%